Combining psychotherapy with craniosacral therapy for severe traumatized patients: A qualitative study from an outpatient clinic in Norway. (March 2020) - Stub, Trine; Kiil, Mona A.; Lie, Birgit; Kristoffersen, Agnete E.; Weiss, Thomas; Hervik, Jill Brook; Musial, Frauke
Highlights: A mixture of different modalities were used by the psychotherapist to access emotions and traumata. Craniosacral therapy reduced physical pain, thereby allowing for the mobilization of the mental resources necessary for psychotherapy. The global aims of treatment were to increase the patients' emotional control and to provide tools to improve self-care. Signs of improvement were defined as the ability to transform and modify negative behaviors and instead do beneficial things (e.g. visiting a good friend). Abstract: Background: Craniosacral therapy (CST) is an established complementary modality for several health complaints. A clinic for psychosomatics in Norway has included CST into a multimodal treatment approach for severely traumatized patients. The aim of this study was to investigate and describe the indications for the use of craniosacral therapy within trauma therapy. Specifically, to explore treatment philosophy, criteria for improvement, treatment aims, and the evaluation of the risk profile of the multimodal treatment approach. Methods: Semi-structured individual interviews (n = 8) and one focus group interview were conducted with the therapists at the Clinic for Psychosomatics, Hospital of Southern Norway, Kristiansand, Norway. The text data were transcribed verbatim, and the analysis of the material was conducted according to conventional and direct content analysis. Results: The therapists at the clinic applied a holistic treatment approach, based on their understanding of mind and body as one entity. To access emotions and traumata, they used a mixture of different treatment techniques. The therapists experienced patients with severe bodily symptoms as being less cognitively present and attributed this to the symptoms craving most mental resources. The craniosacral therapists' specific aims and task within the multimodal trauma therapy was to ease these physical complaints, so that cognitive and emotional resources could be utilized for therapy. The psychotherapists found that emotions and traumata were more accessible after CST. The general treatment goals were to increase symptom tolerance levels and to enable better self-care. Furthermore, the ability to transform negative behaviors and develop positive alternatives were considered to be signs of improvement. Conclusion: The study participants considered that patients with complex traumas, including post‐traumatic stress disorder, seemed to benefit from this multimodal treatment approach and appreciated its' holistic treatment philosophy, including craniosacral therapy. With regard to patient safety, the study participants recommended that craniosacral therapy for severely traumatized patients should only be provided in cooperation with psychotherapists, or other highly qualified health personnel working in specialized institutions.